Behavior modification principles and procedures - Miltenberger, Raymond G.
Uses the principles of behavior modification to teach the procedures of behavior modification, illustrating them with key case studies and examples. This title provides numerous opportunities for students to practice, including practice tests, application and misapplication exercises, and three quizzes at the end of every chapter